The Influence of Temperature and Strain Rate on the Strength Characteristics of Metallic Materials - Kyzioł, L. (Scientific Journal of Gdynia Maritime University, 2017)
The article presents the difference between the quasi-static and dynamic strain of metallic materials. At the high strain rate, stress (strain) in metallic materials moves with specified velocities as a wave. The dynamic deformation is related to the propagation of the wave while the static deformation can be seen as temporary states of equilibrium. At small speed deformations, the body remains in isothermal conditions, while the dynamic strain processes are the adiabatic processes. The concept of the mechanical threshold stress ?^ has been introduced, which is the maximum stress value for the particular type of metallic material for 0 K or, equivalently, infinitely high speed deformation. With the decrease of the temperature, there is a reduction of the dislocation mobility. This phenomenon is associated with a decrease in mobility of atoms in the network at reduced temperatures, which vibrating movement completely stops at 0 K. The concept of the mechanical threshold stress has been illustrated using the calculation example.